HAJ PILGRIMAGE OF MUSLIMS OF CENTRAL ASIA DURING THE YEARS OF SOVIET AUTHORITY - H.B.Haydarova,; Z.G.Aymatova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the issues of pilgrimage of Muslims of Central Asia during the years of Soviet power of the 20th century. The period was studied through comparative analysis of primary sources and literature and relevant scientific conclusions were made.